Effectiveness of Mathematical Learning Model to Stimulate Critical Thinking on Mathematics Learning Outcomes of High School Students - Dafid Slamet Setiana; Rusgianto Heri Santosa (Indonesian Journal of Mathematics Education, 2020)
This study aims to determine the effectiveness of the mathematics learning model to stimulate critical thinking on student mathematics learning outcomes compared to the direct learning model in class XII science students of senior high school in Pacitan. The type of research is quasi-experimental, with a population of all students of class XII IPA of SMA N 2 Pacitan. The sample consists of 28 students of class XII IPA-1 as an experimental class and class XII of IPA-2 of 28 students as a control class. The sampling technique was purposive random sampling. Data collection techniques using the test. The test is a student's initial ability test and a student's mathematics learning outcomes test. The analysis technique of the data used in this study is the t-test, while the analysis of prerequisite tests includes tests of normality and homogeneity tests. The results showed that mathematics learning using the mathematics learning model to stimulate critical thinking was more effectively applied in learning compared to the direct learning model of the mathematics learning outcomes of high school students in terms of the results of the t-test analysis and the average test scores of learning outcomes.